Realisme dalam Worldbuilding Melalui Studi Kasus pada Animasi Kimi no Na wa dan Song of the Sea - Hermanudin, Danika; Ahmad, Hafiz Aziz (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2024)
Worldbuilding has become a center of attention in the entertainment industry, especially in animation. However, attention to worldbuilding studies is still lacking compared to character and narrative. Researchers argue that worldbuilding can be closely related to character creation, reflecting known human traits and characteristics. So that